Hormonal Contraception. Guideline of the DGGG, OEGGG and SGGG (S3 Level, AWMF Registry Number 015/015, January 2020) - Franik, Sebastian; Bauersachs, Rupert; Beyer-Westendorf, Jan; Buchholz, Tina; Bühling, Kai; Diener, Hans-Christoph; Erath, Anke; Fischer, Ronald; Förderreuther, Stefanie; Franz, Heiko B. G.; Hach-Wunderle, Viola; Hadji, Peymann; Harlfinger, Werner; Jaursch-Hancke, Cornelia; König, Klaus; Krämer, Günter; Naumann, Gert; Neulen, Joseph; Oppelt, Patricia G.; Pliefke, Jutta; Rimbach, Stefan; Rott, Hannelore; Schroll, Eckhard; Schumann, Claudia; Segerer, Sabine; Seyler, Helga; Tempfer, Clemens; Thonke, Ines; Toth, Bettina; Wildt, Ludwig; Zotz, Rainer; Stute, Petra; Kiesel, Ludwig (Geburtshilfe und Frauenheilkunde, 2021)
Aims This is an official interdisciplinary guideline published and coordinated by the German Society for Gynecology and Obstetrics (DGGG), the Austrian Society for Gynecology and Obstetrics (OEGGG) and the Swiss Society for Gynecology and Obstetrics (SGGG). The guideline was developed for use in German-speaking regions and is backed by numerous professional societies and organizations. The aim of this guideline is to provide an evidence- and consensus-based overview of the diagnostic approach and the management of hormonal contraception based on a systematic evaluation of the relevant literature.Methods To compile this S3-guideline, a systematic search for evidence was carried out in PubMed and the Cochrane Library to adapt existing guidelines and identify relevant reviews and meta-analyses. A structured evaluation of the evidence was subsequently carried out on behalf of the Guidelines Commission of the DGGG, and a structured consensus was achieved based on consensus conferences attended by representative members from the different specialist societies and professions.Recommendations Evidence-based recommendations about the advice given to women requesting contraception were compiled. The guideline particularly focuses on prescribing contraceptives which are appropriate to womenʼs individual needs, take account of her personal circumstances, and have few or no side effects.Ziel Erstellung einer offiziellen interdisziplinären Leitlinie, publiziert und koordiniert von der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe (DGGG), der Österreichischen Gesellschaft für Gynäkologie und Geburtshilfe (OEGGG) und der Schweizerischen Gesellschaft für Gynäkologie und Geburtshilfe (SGGG). Die Leitlinie wurde für den deutschsprachigen Raum entwickelt und wird von zahlreichen Fachgesellschaften und Organisationen mitgetragen. Das Ziel dieser Leitlinie ist es, durch die systematische Evaluation der relevanten Literatur einen evidenz- und konsensbasierten Überblick über die Diagnostik und das Management der hormonellen Kontrazeption zu geben.Methoden Zur Erstellung der S3-Leitlinie wurde eine systematische Evidenzrecherche durchgeführt zur Adaptation bestehender Leitlinien sowie zur Identifizierung relevanter Reviews und Metaanalysen in PubMed und der Cochrane Library. Im Anschluss wurde eine strukturierte Evidenzbewertung vorgenommen und mittels Konsensuskonferenzen ein strukturierter Konsens von repräsentativen Mitgliedern verschiedener Fachgesellschaften und Professionen im Auftrag der Leitlinienkommission der DGGG entwickelt.Empfehlungen Es wurde eine evidenzbasierte Handlungsempfehlung für die Beratung von Frauen mit Antikonzeptionswunsch erarbeitet. Insbesondere für die Verordnung von Antikonzeptiva, die für die Frau unter Berücksichtigung ihrer Lebensumstände und ihres Risikoprofils individuell geeignet und nebenwirkungsarm oder -frei sind.
Keywords: hormonal contraception; counseling; recommendations; guideline